A Network Pharmacological Approach to Explore the Mechanisms of TongXieYaoFang in Inflammatory Bowel Disease - Wenli You; Mingjuan Li; Aiting Di; Xin Li; Hairui Gao; Cuixia Qiao; Bin Yu; Gang Zhao (Universidade de São Paulo, 2022)
Abstract Inflammatory bowel disease (IBD) is a chronic inflammatory disorder of the intestine, demonstrating an increasing incidence every year. TongXieYaoFang (TXYF) has been used widely in China as a complementary therapy to relieve the symptoms of IBD for hundreds of years. In the present research, a network pharmacology-based approach was used to systematically explore the intrinsic mechanisms of TXYF in IBD at the molecular level. Network pharmacology-based methods, which mainly included database mining, screening of bioactive compounds, target prediction, collection of IBD-related targets, gene enrichment analysis, network construction, and molecular docking, were employed in the present study. Network analysis revealed a total of 108 potential targets derived from 22 component compounds of TXYF, among which 34 targets were common with the IBD-related targets. In the protein-protein interaction (PPI) network, 10 key targets were identified. The gene enrichment analysis suggested that anti-inflammatory processes, such as NF-kappa B signaling pathway and Toll-like receptor signaling pathway, could be the core processes involved in the action of TXYF in IBD. Molecular docking results revealed that three compounds present in TXYF exhibited strong binding affinity for PTGS2. The present study provides novel insights into the molecular mechanisms and network approaches of TXYF action in IBD from a systemic perspective. The potential targets and pathways identified in the present study would assist in further research on the clinical application of TXYF in IBD therapy.